The approach of small and medium manufacturing and processing enterprises to innovation - Lekiqi, Bislim; Afrim Loku; Alberta Tahiri; Idriz Kovaqi (Technium Social Sciences Journal, 2020)
Today’s Kosovo economy, as well as that of the whole world, lives in an extraordinary dynamism, creating and using many new technical-technological and organizational achievements. The demand for innovation is a demand that, as soon as it is met, generates a demand for new innovation, a cycle that will not end. But what is the approach of some manufacturing and processing enterprises (small and medium) in the eastern part of Kosovo to innovation? The answer to this question is the purpose of this article. Research on innovations in Kosovo has been done before, but with a research focus in the district of Prishtina, but not in the eastern region of Kosovo, and there is a long time difference from recent research. The objective of this article is the current approach to innovation. The research was conducted through a face-to-face survey, in which 66 representatives of manufacturing and processing enterprises have participated. The analysis of the results, their comparison leads us to the conclusions and recommendations, information which can serve businesses, state decision-making structures and educational institutions, to compare theory and practice. The article gives to understand that continuous research in this area is an added value.